The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/ma13061336
|View full text |Cite
|
Sign up to set email alerts
|

Deterioration Process of Concrete Exposed to Internal Sulfate Attack

Abstract: Damage to concrete structures with gypsum-contaminated aggregate occurs frequently. Aggregates in much of the southern part of China are contaminated with gypsum. Therefore, in this study, the effects of using different quantities of gypsum-contaminated aggregate on the expansion and compressive strength of concrete were investigated over a period of one year. Two groups of concrete were designed with the gypsum-contaminated aggregate containing different parts of fine and coarse aggregate, respectively. The S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…As shown in the Table 7, the overall cracking load and instability load increase first and then decrease with the increase of dry-wet cycles, and the ratio of the two is 0.7 to 0.9. At the initial stage of corrosion, part of the sulfate radicals enters the concrete to form expansive products such as gypsum and ettringite, which fills the crevices of the concrete, increases the density, improves the crack resistance and limits cracking performance of concrete, and therefore increases the fracture toughness [26,27]. With the increase of corrosion age, the volume of crystallization products expands and exceeds the bearing capacity of the pores, resulting in a large number of micro-cracks, and these micro-cracks form new channels, which accelerate the corrosion rate of sulfate [28].…”
Section: Fracture Toughness Of Modified Concretementioning
confidence: 99%
“…As shown in the Table 7, the overall cracking load and instability load increase first and then decrease with the increase of dry-wet cycles, and the ratio of the two is 0.7 to 0.9. At the initial stage of corrosion, part of the sulfate radicals enters the concrete to form expansive products such as gypsum and ettringite, which fills the crevices of the concrete, increases the density, improves the crack resistance and limits cracking performance of concrete, and therefore increases the fracture toughness [26,27]. With the increase of corrosion age, the volume of crystallization products expands and exceeds the bearing capacity of the pores, resulting in a large number of micro-cracks, and these micro-cracks form new channels, which accelerate the corrosion rate of sulfate [28].…”
Section: Fracture Toughness Of Modified Concretementioning
confidence: 99%
“…It is worth noting that the elevated content of free CaO causes soundness problems in concrete as well as significant temperature increase, (Schlorholtz, 1998). At the same time, high amounts in sulfate ions cause concrete expansion (Zhang et al, 2013), (Ramezanianpour et al, 2020), (Chen et al, 2020). It is well known that the composition of fly ash mainly includes oxides SiO 2 , Al 2 O 3 and Fe 2 O 3 .…”
Section: Raw Materials and Sample Preparationmentioning
confidence: 99%
“…When the RA aggregates get closer, the corrosion products AFt and Gyp is increasing as well. Weifeng [ 24 ] used SEM and EDS to study the microstructure of concrete with different amounts of gypsum-contaminated aggregates. The results showed that the internal cracks of concrete propagate from gypsum to paste during the process of sulfate internal erosion, causing the aggregate to move from the grout and separated from the matrix.…”
Section: Introductionmentioning
confidence: 99%